Determinants of Business Sustainability in Small and Medium Enterprises of Fish Pond Cultivation through Financial Capability Strategy and Organizational Agility - Suryalena, Suryalena; Karneli, Okta; Ruzikna, Ruzikna; Mandataris, Mandataris; Febrian, Achmad Fajri (Budapest International Research and Critics University, 2022)
Micro, Small and Medium Enterprises (MSMEs) in the aquaculture business sector in Indonesia are able to be resistant in facing global economic changes, and are able to become the backbone of the local and national economy. In addition to being an opportunity, changes in the business environment tend to be uncertain, and become a threat that is difficult to control. The failure of SMEs in the aquaculture sector to adapt will threaten business sustainability in the future. So, it is necessary to have a strategy at the organizational level in managing these threats. This article attempts to measure the implementation of financial capability and organizational agility as antecedents of business sustainability. The unit of analysis that was measured was MSME fishpond cultivation in Kampar Regency. Based on Slovin's formula, the number of samples needed is 98 people. The data analysis process uses the SEM method through a partial least square approach. Based on the results of the analysis, fish pond cultivation SMEs in Kampar Regency have implemented all dimensions of financial capability as a strategy to take advantage of opportunities that arise in the market to create business sustainability. The results of data processing through the SEM method, one of the dimensions of the construct, namely organizational agility, gets a weak significance or probability value on business sustainability. This proves that fish pond cultivation SMEs have not optimized all their resources to adapt to changes in the business environment. The findings of this study indicate that with financial management in the aspect of human resources, agility characteristics will be created where business actors/fish pond farmers can quickly adapt to changes in technology that are currently developing, through the use of venture financing services from non-bank financial institutions.